Burn Injury Characteristics and Outcomes among Hospitalized Patients in Tertiary Burn Unit (Medico Legal Update, 2020)
Background: Burn Injuries constituted an important high priority health problem especially in little andmedium salary republics including Iraq.Objective: Identify the characteristics of burn injuries and its outcomes among patients admitted to Al-HillaTeaching Hospital burn unit–Babylon Province Iraq.Method: This was observational cross sectional hospital based study, burn injury data were collected fromthe interview of burn patients admitted to burn unit of Al Hilla Teaching Hospital,Babylon Province, Iraqduring the last four months during the year 2019, using special data collection questionnaire included; burnpatients demographic characteristics, period of hospital stay (days), size of total body surface areas, degreesof burn injuries, types of treatment and the outcomes.Results: The highest proportion of cases were males, the majority of patients were young adults andchildren, about four fifth of cases were rural dwellers (78%). The means and standard deviations of durationof hospitalization and total surface areas were 5.72+53 days and 21,9+21.1 respectively, about two thirdsof the study group were second and or third degrees burn, only 12% of patients were treated surgically bywound excision and skin graft, 67% of patients were cured while the case fatality rate was 9%.Conclusion: Children, males and poorly educated patients were the majority of cases, about nine in tenthwere treated conservatively and about two thirds of cases were cured.